2022
DOI: 10.1007/s00268-022-06656-0
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy Needs for Implementation of a Colorectal Cancer Screening Program in Ukraine

Abstract: Background In Ukraine, there is no established colorectal cancer screening program. We aimed to project the number of screening colonoscopies needed for implementation of various CRC screening strategies in Ukraine. Methods We modified a previously developed Markov microsimulation model to reflect the natural history of adenoma and CRC progression among average-risk 50-74-year-olds. We simulated colonoscopies needed for the following screening strategies: no screening, fecal occult blood test yearly, FOBT year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…28 Our previous study that estimated the number of screening colonoscopies required for implementing various CRC screening strategies in Ukraine found that the fewest colonoscopies were needed with a FOBT program, while the most were required with a colonoscopy program, highlighting significant variations in resource requirements on the basis of the chosen screening test. 29 In another study in Ukraine, we found inconsistent CRC staging practices and varied adjuvant treatments, likely because of limited resources for providers and the high cost of patient care in the region. 30 In Our study faces several limitations.…”
Section: Discussionmentioning
confidence: 78%
“…28 Our previous study that estimated the number of screening colonoscopies required for implementing various CRC screening strategies in Ukraine found that the fewest colonoscopies were needed with a FOBT program, while the most were required with a colonoscopy program, highlighting significant variations in resource requirements on the basis of the chosen screening test. 29 In another study in Ukraine, we found inconsistent CRC staging practices and varied adjuvant treatments, likely because of limited resources for providers and the high cost of patient care in the region. 30 In Our study faces several limitations.…”
Section: Discussionmentioning
confidence: 78%
“…The manuscript by Welten et al projects the number of colonoscopies necessary for a national colorectal cancer (CRC) screening program for Ukraine for average risk age 50-74 individuals using an elegant Markov microsimulation model that takes into consideration the adenoma to carcinoma progression [1]. These data would have gone a long way to address cancer care in Ukraine where 2020 cancer statistics found that colorectal cancer was the most common new cancer diagnosed and fourth most common cause of cancer-related death [2].…”
mentioning
confidence: 99%
“…These data would have gone a long way to address cancer care in Ukraine where 2020 cancer statistics found that colorectal cancer was the most common new cancer diagnosed and fourth most common cause of cancer-related death [2]. Pre-conflict Ukraine had no formal cancer screening programs, but health care reform was underway as directed by Parliament to strengthen primary care and improve earlier detection of disease [1]. In 2020, the Ukraine Ministry of Health started a national breast screening program with expansion of mammography services with assistance from the World Health Organization (WHO) and France to help address national cancer statistics, showing that 1 in 4 breast cancers were diagnosed in late stage of disease which has significant negative outcome implications for patients [3].…”
mentioning
confidence: 99%